Subject-controlled stimulation of dorsal genital nerve to treat neurogenic detrusor overactivity at home - Opisso, Eloy; Borau, Albert; Rijkhoff, Nico J.M. (Neurourology and urodynamics, 2013)
Aims To investigate the effects of subject controlled dorsal genital nerve (DGN) electrical stimulation on neurogenic detrusor overactivity (NDO) in subjects at home. Methods Subjects underwent a 5‐day study at home with DGN stimulation. Stimulation was provided with surface electrodes placed either on the dorsal penile shaft in males and on or close to the clitoris in females. The days 1 and 5 were with no stimulation whereas days 2–4 were with stimulation. Two urodynamic studies were performed at the beginning and at the end of the study. A bladder diary was obtained. Results Eleven subjects with NDO and with urge incontinence were included. One subject stopped the protocol before the end of the 5‐day trial and two did not undergo the second urodynamic study. The subjects showed a statistically significant increase in bladder capacities compared to baseline (P = 0.047). Mean volume per day voided significantly increased over the study within the subjects. Differences between day 1 and day 5 were statistically significant (P = 0.028). Conclusions The feasibility and the globally positive outcomes of the study indicate that the stimulation of the dorsal genital nerve can be an option for the treatment of the NDO. Neurourol. Urodynam. 32: 1004–1009, 2013. © 2012 Wiley Periodicals, Inc.